2013
DOI: 10.1038/nature12009
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional imaging of dislocations in a nanoparticle at atomic resolution

Abstract: Dislocations and their interactions strongly influence many material properties, ranging from the strength of metals and alloys to the efficiency of light-emitting diodes and laser diodes. Several experimental methods can be used to visualize dislocations. Transmission electron microscopy (TEM) has long been used to image dislocations in materials, and high-resolution electron microscopy can reveal dislocation core structures in high detail, particularly in annular dark-field mode. A TEM image, however, repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
275
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(301 citation statements)
references
References 33 publications
5
275
0
11
Order By: Relevance
“…Although high-resolution atomic force microscopy enables individual dislocations to be identified at the surfaces, it falls short of providing atomic resolution of their cores 9 , impeding a ready inference of their core properties. In contrast, advanced transmission electron microscopy (TEM) is in principle able to directly resolve individual embedded dislocation cores with single-atom sensitivity [10][11][12][13] , particularly in the annular darkfield mode 10,11 . This leads to a far greater understanding on the correlation between the dislocation cores in real materials and their mechanical, optical, and electronic behaviours 12,14 .…”
mentioning
confidence: 99%
“…Although high-resolution atomic force microscopy enables individual dislocations to be identified at the surfaces, it falls short of providing atomic resolution of their cores 9 , impeding a ready inference of their core properties. In contrast, advanced transmission electron microscopy (TEM) is in principle able to directly resolve individual embedded dislocation cores with single-atom sensitivity [10][11][12][13] , particularly in the annular darkfield mode 10,11 . This leads to a far greater understanding on the correlation between the dislocation cores in real materials and their mechanical, optical, and electronic behaviours 12,14 .…”
mentioning
confidence: 99%
“…For polycrystalline or amorphous materials, such approaches are not applicable and a full tomographic tilt series needs to be carried out. Near-atomic resolution of single-metallic polycrystalline particles has been first demonstrated on gold nanoparticles 15 , and more recently Chen et al 16 have mapped 3D dislocations in platinum nanoparticles at atomic resolution using very strong filtering in the Fourier domain. This approach has been used to some success, but has also led to some controversy 17 and, moreover, is not necessary when careful considerations in the reconstruction are applied to low-noise experimental data.…”
mentioning
confidence: 99%
“…33 In this study, the Pt atomic columns were clearly observed and the Fe Kagomé layer (3/4 monolayer) and the 1/4 monolayer were also 34 Recently, a resolution of 2.4 Å was obtained for Au single crystalline NP 35 and Pt nanodecahedra 36 with twin boundaries. Some advanced algorithms, such as the Compressive Sensing algorithm, were utilized to achieve better resolution for Au nanorods (NRs).…”
Section: Synthetic Methodologies Of Nhssmentioning
confidence: 87%